2009
DOI: 10.1099/ijs.0.004515-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus tepidarius sp. nov., a thermotolerant yeast species isolated from a stream from a hot-spring area in Japan

Abstract: Anamorphic basidiomycetous yeast strains M9962T and M9963 were isolated from water samples collected from a small stream in Ohwakudani, Hakone, a hot-spring area in Japan. These belonged to a single species and were phylogenetically closely related to Bullera lagerstroemiae, although the ability to form ballistoconidia was not observed. Based on sequence analyses of the D1/D2 domain of the LSU rDNA and ITS regions and differences in G+C content, the name Cryptococcus tepidarius sp. nov. Takashima, Sugita, Tori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
(23 reference statements)
1
17
0
1
Order By: Relevance
“…Species with low temperature optima are more frequent among basidiomycetes (Robert et al, ). The highest growth temperature (47.7°C) among non‐human‐related basidiomycetous yeasts was recorded for Takashimella tepidaria (formerly Cryptococcus tepidarius ), which has been isolated from a hot‐spring area (Takashima, Sugita, Toriumi, & Nakase, ). The former genera Cryptococcus and Rhodotorula were the most commonly reported yeasts in early investigations carried out in cold habitats (reviewed by Buzzini et al, ).…”
Section: Frequent Yeasts From Extreme Environments: Tough Survivorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Species with low temperature optima are more frequent among basidiomycetes (Robert et al, ). The highest growth temperature (47.7°C) among non‐human‐related basidiomycetous yeasts was recorded for Takashimella tepidaria (formerly Cryptococcus tepidarius ), which has been isolated from a hot‐spring area (Takashima, Sugita, Toriumi, & Nakase, ). The former genera Cryptococcus and Rhodotorula were the most commonly reported yeasts in early investigations carried out in cold habitats (reviewed by Buzzini et al, ).…”
Section: Frequent Yeasts From Extreme Environments: Tough Survivorsmentioning
confidence: 99%
“…Several yeasts have been isolated from naturally acid (pH 1–3) environments. Among them some acidophilic or acidotolerant species are able to grow at or below pH 2, namely Kazachstania exigua , Pichia kudriavzevii (former Candida krusei ), Pichia membranifaciens , S. cerevisiae and Zygosaccharomyces rouxii in the Ascomycota and R. glutinis , Slooffia tsugae , Takashimella formosensis and Takashimella tepidaria in the Basidiomycota (Nguyen et al, ; Pitt & Hocking, ; Péter et al, ; Raspor & Zupan, ; Takashima et al, ; Russo et al, ; Gadanho et al, ). Yeasts tolerating high pH values are mainly reported as members of the genera Barnettozyma , Cyberlindnera and Wickerhamomyces (Agno, ; Deak, ; Péter et al, ).…”
Section: Frequent Yeasts From Extreme Environments: Tough Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast diversity has been extensively investigated (3). Several types of yeast have been isolated from these extreme acidic environments to date; e.g., Rhodotorula glutinis (4), Candida maltosa (5), and Cryptococcus tepidarius (6). In Saccharomyces cerevisiae, yeast genes involved in responses to acid stress have been studied (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The ascomycetous yeast species Ogataea thermophila was reported to grow at 50°C and, therefore, has the highest growth temperature known to date (Shin et al ., ; Péter et al ., ); however, this strain has a unique 26S rRNA partial sequence that separates it from other ascomycetous yeasts. Takashima and colleagues () reported that Cr. tepidarius , isolated from a stream from a hot‐spring area in Japan, was able to grow at 47°C and, therefore, has the highest maximum growth temperature reported so far for basidiomycetous yeast.…”
Section: Discussionmentioning
confidence: 99%